Forensic Tool Comparison on Instagram Digital Evidence Based on Android with The NIST Method - Riadi, Imam; Yudhana, Anton; Putra, Muhamad Caesar Febriansyah (Universitas Negeri Semarang, 2018)
The growth of Android-based smartphone users to access media in communicating using Instagram social media is very fast. Activities are carried out when using Instagram social media in communicating to share information such as sending chat texts and pictures. A large number of Instagram users make this application vulnerable to abuse of Instagram such as pornography crimes from Instagram users. This case can be forensic to get digital evidence in the form of chat text and pictures from Instagram messenger is a feature of Instagram. The investigation in this study uses the National Institute of Standards and Technology (NIST) method which provides several stages of collecting, examining, analyzing, reporting while forensic tools use forensic oxygen and axiom magnets. The results of the recovery and comparison of data result using Oxygen forensics and Axiom Magnets obtained digital evidence in the form of data in the form of images and chat. The data obtained by Magnet Axiom is 100% while forensic oxygen is 84%. These data are the results of the performance of both forensic applications in obtaining digital evidence that has been deleted from the Instagram messenger.